A criação de alegorias de carnaval : das relações entre modelagem matemática, etnomatemática e cognição - Madruga, Zulma Elizabete de Freitas (2012)
This research provides a comparative analysis among the creation processes of carnival floats, mathematical modeling procedures, mental models and ethnomathematics. It was found, through interviews with the carnival, the responsible person for designing and building floats for a samba school parade that these procedures are closely linked. It was also indicated ways to use mathematical modeling and information technologies and communication as a pedagogical practice with this social group identifiable in order to value their culture, that is, its ethnomathematics. The methodology used in this study was the mapping of educational research, as Biembengut (2008), which was divided into for steps: identification map, which are the objectives of this ethnographic research, as well as justifications and methodological procedures, theoretical map, which justified the search through the definitions and theories about mental models, mathematical modeling and ethonomathematics; field map, in which the work reported in the a samba school shed of the special municipality of Porto Alegre (RS) where data were collected through observations and interviews were explained; map analysis, in which these data were studied, showing that the goals and objectives previously established have been achieved. Considerations and recommendations about education suggest ways to use the subject matter in the classroom, through modeling and ethnomathematics.